Global Phase Portraits for the Kukles Systems of Degree 3 with â.,¤2-Reversible Symmetries - Dias, Fabio Scalco (2021)
We provide the normal forms, the bifurcation diagrams and the global phase portraits on the Poincaré disk of all planar Kukles systems of degree 3 with Z2-symmetries.